(untitled) (CIPEEX, 2022)
THIS IS A WORK CARRIED&NBSP; OUT IN ORDER TO SHOW THE IMPORTANCE OF BIODIVERSITY CONSERVATION, WITH CONCRETE DATA, THROUGH THE CREATION OF RPPNS, AND SPECIALLY THE RPPNS LOCATED IN THE MUNICIPALITY OF PIRENOPOLIS, ABOUT THE WHOLE OPERATION OF THERE.